A novel off–on fluorescent probe for sensitive imaging of mitochondria-specific nitroreductase activity in living tumor cells. Issue 20 (5th May 2017) - Huang, Bo; Chen, Wen; Kuang, Yong-Qing; Liu, Wei; Liu, Xian-Jun; Tang, Li-Juan; Jiang, Jian-Hui
Abstract : We have developed a novel fluorescent probe of a benzoindocyanine probe (BICP), which is able to target mitochondria and realize sensitive and selective detection of NTR. Abstract : Sensitive and selective detection and imaging of nitroreductase (NTR) in cancer cells is of great importance for better understanding their biological functions. Since there are a few fluorescent probes concerning NTR activity specifically located in mitochondria, we developed a novel fluorescent benzoindocyanine probe (BICP) for mitochondrial NTR activity monitoring and imaging via extending a benzoindole moiety into a benzoindocyanine based fluorophore (BICF) with a strong intramolecular charge transfer (ICT) effect and incorporating 4-nitrobenzyl as a fluorescence-quenching and enzyme-responsive moiety. Live cell imaging of HeLa and A549 demonstrates that the developed BICP is able to realize sensitive and selective mitochondrial NTR activity probing with high-contrast "off–on" fluorescence. These findings implied the great potential of the developed probe for monitoring mitochondrial-specific NTR activities in living cells and related applications in cell biology.